Slide positivity, trends, and risk factors of febrile Plasmodium vivax malaria along the Thailand-Myanmar border, 2018–2023 - Pyae Linn Aung; Nattawan Rachaphaew; Piyarat Sripoorote; Khaing Zin Zin Htwe; Kritsana Suk-aum; Jaranit Kaewkungwal; Saranath Lawpoolsri; Liwang Cui; Jetsumon Sattabongkot (Infectious Diseases of Poverty)
Abstract Background Plasmodium vivax is the predominant malaria species in many Southeast Asian countries. Eliminating all human malaria species by 2030 requires greater focus on P. vivax, with targeted measures to address its unique challenges. This study evaluated slide positivity rates, temporal trends, and risk factors associated with febrile P. vivax infections in a malaria-endemic district along the Thailand-Myanmar border. Methods This study employed a community-based longitudinal surveillance design over six years (January 2018–December 2023). Data were collected through routine passive case detection at field malaria clinics using extended, standardized case record forms. Malaria diagnosis was conducted via microscopy examination. Descriptive statistics and logistic regression models were used for data analysis. Results Among 13,347 febrile malaria-suspected patients, the cumulative slide positivity rate for P. vivax was 11.0%. Although no distinct seasonal peaks were observed, P. vivax cases generally increased in April and again in November and December. Multivariable logistic regression analysis identified several significant risk factors for febrile P. vivax infection, including school-aged children (5–14 years) (aOR: 1.56, 95% CI: 1.24–1.97), working-age adults (15–34 years) (aOR: 1.43, 95% CI: 1.02–2.00), males (aOR: 1.19, 95% CI: 1.06–1.35), Myanmar nationals (aOR: 2.37, 95% CI: 2.01–2.80), and other non-Thai nationals, such as individuals from Laos and Cambodia (aOR: 5.50, 95% CI: 3.36–8.90). A history of malaria (aOR: 1.59, 95% CI: 1.38–1.83), recent travel within two weeks (aOR: 2.38, 95% CI: 1.94–2.92), and engagement in livestock-related occupations (aOR: 2.49, 95% CI: 1.14–5.35) were also associated with higher odds of infection. In contrast, being unemployed (aOR: 0.55, 95% CI: 0.36–0.81), working in occupations such as maid, driver, or teacher (aOR: 0.78, 95% CI: 0.66–0.93), and consistent use of bed nets (aOR: 0.39, 95% CI: 0.30–0.51) significantly reduced infection risk. Conclusions This study identified a relatively high slide positivity rate of febrile P. vivax infection in a malaria-endemic district in western Thailand along the Myanmar border. Strengthening malaria surveillance, targeting high-risk populations, ensuring treatment adherence, and promoting early care-seeking behavior are crucial for reducing P. vivax transmission and advancing malaria elimination efforts. Graphical abstract